Lactate in Bitches with Pyometra - Volpato, R. [UNESP]; Rodello, L. [UNESP]; Abibe, R. B. [UNESP]; Lopes, Maria Denise [UNESP] (Wiley-Blackwell, 2012)
Lactate is a compound produced by the anaerobic metabolism of glucose, and hyperlactataemia occurs when the rate of production of lactate exceeds the rate of elimination. This occurs in situations of hypoxia and tissue hypoperfusion. Lactate has been considered a useful prognostic indicator in critically ill patients. Pyometra is a disease of adult female dogs characterized by inflammation of the uterus with an accumulation of exudate, which occurs during the luteal phase. It is one of the most common diseases that occur in the genital tract of female dogs. A total of 31 dogs were diagnosed with pyometra. The diagnosis was confirmed at ultrasonography. of the 31 dogs, 25 females had open cervix pyometra and six had closed cervix pyometra. Plasma lactate concentrations were determined by an enzymatic colorimetric method. The average concentration (+/- SD) of plasma lactate in all 31 bitches with pyometra was 3.55 +/- 0.46 mm. Healthy dogs had plasma lactate concentrations between 0.3 and 2.5 mm (mean +/- SD). Concentrations ranged from 0.8 to 2.9 mm when plasma lactate was measured with a portable device and 0.42.6 mm with the blood gas analyser. Even though plasma lactate values vary between several studies and equipment used to measure concentrations, our results for dogs with pyometra are higher indicating hyperlactataemia (Thorneloe et al. , Can Vet J 48, 283288). Plasma lactate in dogs with closed cervix pyometra was mean +/- SD and in dogs with open cervix pyometra, it was mean +/- SD. The plasma lactate concentration in dogs with pyometra was higher than in healthy bitches, and there was no influence of patency of the cervix on the concentration of plasma lactate concentrations. Plasma lactate concentrations were similar for animals with open and closed pyometra (3.54 +/- 0.52 to 3.64 +/- 1.03 mm).